PENELUSURAN SEJARAH PUKULAN GANTUNG INSTRUMEN TAR GRUP HADRAH HUBBUL WATHAN KELURAHAN SUNGAI JAWI DALAM - Chaidir, Chaidir; Fretisari, Imma; Silaban, Christianly Yery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The purpose of this research is to describe the history and the development and the concept of learning by pukulan gantung of Hadrah Hubbul Wathan Group.This research used qualitative historical descriptive method and history approach. The sources of this research are Awaluddin Hamdan, Anwar Dja’far, and Abdul Halim who knew about pukulan gantung of Hubbul Wathan hadrah group also several hadrah artists who lived in every districts in Pontianak. The technique which used were observation, interview, and documentation. According to the data analyzed, it can be concluded that pukulan gantung is a syncopation from the term of tar instrument played in Pontianak. It was created by Hubbul Wathan hadrah group in 2002 till 2005. This hit has its own uniqueness to Hubbul Wathan hadrah art group and another hadrah artists in Pontianak. They interpretated that hit as the climax in hadrah playing. In 2009 to 2013 pukulan gantung started to spread out to another different art groups in every districts in Pontianak until now. Keywords: history, pukulan Gantung, Hubbul Wathan.